Acute enterovirus infection followed by myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and viral persistence. Issue 2 (14th October 2009) - Chia, J; Chia, A; Voeller, M; Lee, T; Chang, R
Abstract : Aims: Enteroviruses are well-known causes of acute respiratory and/or gastrointestinal infections and non-specific flu-like illness. Although enterovirus protein, RNA and non-cytopathic viruses have been demonstrated in the stomach biopsies of patients with myalgia encephalomyelitis/chronic fatigue syndrome (ME/CFS), causality for chronic diseases is difficult to establish without having well-documented cases of acute enterovirus infections. The aim of this study was to link acute enteroviral infection to viral persistence in patients with ME/CFS. Method: Patients admitted to the hospital with acute febrile illnesses were screened for enteroviral infections. Acutely infected patients were followed longitudinally, and those who developed symptoms of ME/CFS underwent oesophagogastroduodenoscopy and biopsies of the antrum to document viral persistence by immunoperoxidase staining for viral protein and viral RNA assay. Results: Three representative patients with different manifestations of acute enterovirus infections progressed to have chronic symptoms of ME/CFS. Persistent viral infection was demonstrated in the antrum years later. Conclusion: After acute infections, enteroviruses can persist in patients resulting in manifestation of ME/CFS. Chronic enterovirus infection in an immunocompetent host may be an example of a stalemate between attenuated, intracellular viruses and an ineffective immune response.